Indonesia Naval Technology College STTAL Postgraduate International Conference - Proceedings of STTAL Postgraduate International Conference " DEFENSE SCIENCE AND TECHNOLOGY” - STTAL POSTGRADUATE (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2018)
Proceeding of STTAL Postgraduate International Conference “DEFENSE SCIENCE AND TECHNOLOGY” Field : Operation Research. Logistics Management. Policy and Strategy.